2011
DOI: 10.1159/000328342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Long-Term Clarithromycin Treatment in Adult Chinese Patients with Chronic Rhinosinusitis without Nasal Polyps

Abstract: Objective: To evaluate the efficacy of long-term clarithromycin (CAM) treatment in adult Chinese patients suffering from chronic rhinosinusitis without nasal polyps (CRSnNP). Methods: Thirty-three CRSnNP patients were enrolled and subjected to CAM treatment for 12 weeks (250 mg daily). The total nasal symptom scores (TNSS), nasal resistance and inflammatory mediators including interleukin (IL)-8 and myeloperoxidase (MPO) were evaluated at weeks 0 and 12. Quality of life (QoL) was assessed in all patients by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…5,6,[11][12][13] Macrolide therapy has been shown to have a slow onset, with ongoing improvement until several months after the start of therapy. 3 However, we have observed significant clinical improvement in chronic rhinosinusitis patients after clarithromycin Data values represent median scores and interquartile ranges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,[11][12][13] Macrolide therapy has been shown to have a slow onset, with ongoing improvement until several months after the start of therapy. 3 However, we have observed significant clinical improvement in chronic rhinosinusitis patients after clarithromycin Data values represent median scores and interquartile ranges.…”
Section: Discussionmentioning
confidence: 99%
“…As we have previously described, the Sino-Nasal Outcome Test 20 is a validated, rhinosinusitis-specific QoL instrument, in which patients are asked to answer 20 questions regarding their nasal symptoms and QoL. 6 Cytokine levels. Nasal secretions were collected (in the manner previously described 6 ) at the three time points.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been seen previously, 754 patients with AR did not have as robust a response to macrolide therapy. Luo et al 759 treated CRSsNP patients with clarithromycin and found improved nasal symptom scores, as well as reductions in IL-8 and myeloperoxidase in nasal secretions. Macrolide therapy was found to be more effective in patients with high IL-8 levels prior to treatment.…”
Section: Viie4 Crssnp Management: Antibioticsmentioning
confidence: 99%
“…Further, some patients are nonresponders after treatment with corticosteroids for 3 months and receive a functional endoscopic sinus surgery. The recourse required by these patients implies that the level of TGF-β1 is not modulated by corticosteroid treatment, indicating that corticosteroids show no effect on TGF-β1 expression in CRS, as suggested by the results of computed tomography/endoscopy, histopathologic examination, and patients’ complaints [35,36,37]. …”
Section: Potential Therapeutic Applications In Crsmentioning
confidence: 99%